Signs of Spiritual Crisis or Evidence of Unexpected Commitment? Attitudes to Compulsory Church Parades in the First AIF1. (21st April 2016) - Reynaud, Daniel
Abstract : This study explores the attitude of Anzac soldiers to the compulsory Church Parades, drawing evidence from a reading of the diaries and letters of over a thousand soldiers. It examines the complex reactions to Church Parade and draw conclusions about the varied attitudes of soldiers who recorded attending Church Parades in their letters and diaries. Far from producing definitive evidence for the irrelevance of religion to Australian soldiers during the Great War, the study highlights the range of religious attitudes, including the surprising number of soldiers who recorded positive responses to these parades. Even negative attitudes to Church Parades could stem not just from the secular soldiers, but also from the disappointment which religiously committed soldiers felt during times of forced religious activity. Responses to compulsory religious activities in the army do not uniformly support the irreligious nature of the Anzacs. Rather they show that a significant minority — larger and more expressive than generally imagined, and not all of them devout — valued religion and recorded their sentiments about it in their personal writings.